Death due to Pulmonary Fat Embolism Case Report - İlhan, Ramazan and Özen, Bahadır and Beder, Cemil and Öğüt, Oğuzhan and Bütün, Celal and Arslan, Sulhattin and Beyaztaş, Fatma Yücel (The Bulletin of Legal Medicine, 2014)
Fat embolism, generally serious trauma or surgery later, is to pass to the systemic circulation of the oil droplets released from the bone marrow or the soft tissues. It is developed after long bone fractures in the young, but also after hip fracture in the elderly. The clinical table occurred usually 24-48 hours after trauma may be such as light or can progress to respiratory failure and also death. In this case, the 84-year-old woman has been admitted to the hospital due to the traffic accident with complaint pains in the left arm and the left pelvic area. On orthopedic consultation, she was made the close reduction because of the left shoulder dislocation, the left supracondylar humerus fracture and the left ramus pubic fracture, and then, she was discharged to her house. She was reported as “dead” at the house after about three hours from accident. In autopsy of forensic case regarded as suspicious death, it was seen the hemorrhagic featured liquid out on the lung sections, the left shoulder dislocation, the left supracondylar humerus fracture and the left ramus pubic deplase fracture. In the postmortem histopathological examination, it was determined the stage IV of fat embolism in the interstitial capillary lumens in the lungs and the common bone marrow embolism in the medium-sized pulmonary vascular. According to the story of the event, the contents of the medical records, and the macroscopic-histopathological examination findings during autopsy; the death of the case occurred as a result of fat embolism in the lung together with extremity fractures depending on the general body trauma after the traffic accident. After post-traumatic bone fractures, early fixation and immobilization of the fractures is important to prevent the formation of fat embolism. Being careful follow-up and treatment of the cases is important in terms of prevention of the medical practice. Also, in the cases, the broken bones in the accident identified and evaluated as suspicious death; the contribution of the autopsy and the postmortem histopathological examination is clear on determining the diagnose. Key Words: Fat embolism, trauma, forensic medicine, autopsy, suspicious death.